Powering Multiple Gas Condensate Wells in Russia’s Arctic: Power Supply Systems Based on Renewable Energy Sources - Gennadiy Stroykov; Alexey Y. Cherepovitsyn; Elizaveta A. Iamshchikova (Resources, 2020)
Using renewable energy off-grid power supply and choosing the right equipment that meets the operating conditions in the Arctic can provide companies with reliable power sources for producing gas at facilities located in remote areas and will reduce capital and operating costs associated with the construction of power transmission lines. For more than 15 years, a remote control system powered by renewable energy has been used in parallel with power transmission lines by Gazprom to operate its multiwell pads in Russia’s Far North, which validates the relevance of this study. The subject of the study is a group of gas condensate wells that consists of four multiwell pads operated by Wintershall Russland GmbH. The article discusses a stand-alone renewable-based power system as an option for powering remote oil and gas production facilities. The procedures used in the study include calculating such parameters as power output and power consumption, choosing equipment, describing the design features of a power supply system for a multiwell pad, conducting an economic assessment of the project, comparing different power supply options, analyzing project risks, and developing measures to mitigate these risks.